Multiple Leiomyomas in a Patient with Benign Metastasizing Leiomyoma: A Case Report - Liu, Shuangjiao; Zhou, Wenming; Fu, Weidong (Current Medical Imaging, 2022)
Introduction: Benign metastasizing leiomyoma (BML) is a rare disease and mostly affects females with a history of uterine leiomyoma, and particularly the presence of multiple leiomyomas in BML patients is extremely rare. Case Presentation: This paper reported the clinical and imaging data of a BML patient with multiple leiomyomas involving bilateral pulmonary, mediastinum, pericardium, spine, peritoneum, and left thigh. Multiple BML lesions exhibited consistent imaging examinations, significantly improving the delayed phase enhancement. After multi-stage targeted therapy for multiple systemic metastases and the development of drug resistance, the patient was treated with hysterectomy and bilateral adnexectomy along with letrozole-based endocrine therapy. BML lesions, both pulmonary and mediastinum, became significantly smaller than before. Conclusion: This paper aims to analyze the imaging and clinical features of multiple leiomyomas in this BML case, thus strengthening the understanding of the rare type of leiomyoma for effective preoperative diagnosis and clinical treatment. Furthermore, it is noteworthy that gynecologists should avoid the manifestation of BML when performing uterine fibroids surgery.
Keywords: pulmonary